Study of DHF G function algorithm used for DHF systems - CHEN Yong; ZHAO Hang-sheng (Tongxin xuebao)
How to construct a set of DFH G function algorithm had presented.The function was easy to be generated.The methods of the parameter selection for the G function were given in theory,and the quality of the uniformity usage of the frequency points in the DFH system range was analyzed.Lastly,the performances of the FH pattern was tested and some beneficial conclusions were derived.